Propuesta para el mejoramiento del desempeño de un tripulante de cabina - Agreda Fernandez, Maria Elena (2011)
The present study is a professional report that describes narratives and experiences taken from the real life of a cabin crew member, of a flight company, during the three phases of attention to passengers, which has been used, as inputs, to prepare a proposal to enhance the aviation company. Additionally, a survey was applied to a purpose sample of 40 participants. The origins of the role of a cabin crew member, the importance of such role for the security and the quality of the service offered to passengers were part of the results obtained. The proposal includes two main objectives: first, to enhance the image that the passengers have about the functions of a cabin crew member, through diffusion activities; and, second to recommend the inclusion of academic content in the formation plan and training of the cabin crew members to be. Finally, conclusions and recommendations are presented.